Offline system analysis of high frequency digital signal / Mohd Zaidi Che Mat - Che Mat, Mohd Zaidi (2009)
This project highlights the significant of the high frequency (HF) communication system in communication field. With a frequency spectrum between 3 to 30 Mhz an ionosphere often reflects the signal frequency very well during transmitting the signal. Hence, the HF communication can be done in long distance transmission. Although, HF communication is applied in radio communication but the HF technology application is still limited because it only involve in certain application. By taking these factors into consideration the idea is generate in order to enhance this application technology. As a result, a research must be conducted to make the HF communication system enhanced in accordance with the development of communication technology. In order to enhance this technology application a system to analysis HF signal should be created to help in developing this communication technology. Concerning to this issues, the system was develop to analyze HF signal. The system is operating in offline mode. The system only capable to read HF signal in form of *.wav file. The system also capable to filter signal so that the process of analyze the signal can be done smoothly. With the periodogram and spectrogram technique the system able to produce a result analysis accurately because it will illustrate the valuable information contain in the signal such as frequency, energy of the signal and the duration of the signal. In addition, the modulation type of the signal and the bit rate also can be determined.